2021
DOI: 10.3390/su132212832
|View full text |Cite
|
Sign up to set email alerts
|

Restored Coastal Habitat Can “Reel In” Juvenile Sportfish: Population and Community Responses in the Indian River Lagoon, Florida, USA

Abstract: Coastal habitats are declining worldwide, which has impacted economically important fisheries, especially in the Indian River Lagoon, Florida. As a result, extensive intertidal oyster reef and living shoreline restoration projects have been implemented. Restoration can also theoretically benefit predator populations, but this relationship is understudied. Here, the impact of habitat restoration on juvenile predatory fish (i.e., sportfish) populations (abundance) and communities (species richness, diversity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 52 publications
(111 reference statements)
2
33
0
Order By: Relevance
“…Lenihan et al [58] found that piscivorous fish abundances around restored reefs were similar to those around natural reefs in a North Carolina estuary. In Mosquito Lagoon, Loch et al [59] also found an increase in juvenile sport fish around restored reefs. The ability of these restored reefs to support higher trophic-level organisms such as piscivorous fish and birds indicates success in restoring the trophic structure on these reefs.…”
Section: Bird Abundance and Behaviorsmentioning
confidence: 94%
“…Lenihan et al [58] found that piscivorous fish abundances around restored reefs were similar to those around natural reefs in a North Carolina estuary. In Mosquito Lagoon, Loch et al [59] also found an increase in juvenile sport fish around restored reefs. The ability of these restored reefs to support higher trophic-level organisms such as piscivorous fish and birds indicates success in restoring the trophic structure on these reefs.…”
Section: Bird Abundance and Behaviorsmentioning
confidence: 94%
“…bulkheads and riprap) using a seaward breakwater consisting of stacked oyster shell bags to attenuate wave energy, and shoreward planted vegetation (i.e. cordgrass Spartina alterniflora and mangrove Rhizophora mangle ) to reduce shoreline erosion (see Donnelly et al 2017; Loch et al 2021). Three stabilized shorelines were compared to two control (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…1). Oyster density, reef height, and shoreline vegetation percent cover data were collected (Donnelly et al 2017;Loch et al 2021; Walters et al 2021). Sportfish were captured using a bag seine (21.3 × 1.8 m; 3.175 mm mesh) pulled parallel to the site prior to and following restoration at 1, 2, 4, 6, 8 and every 12 weeks thereafter for up to 3 years.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations